TANGGUNG JAWAB HUKUM PENERBIT UANG ELEKTRONIK TERHADAP KERUGIAN NASABAH PENGGUNA UANG ELEKTRONIK DI BANK MANDIRI - Salsabila Sekar Wahri; Ria Safitri; Faris Satria Alam (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study seeks to explain the topic of the legal liability of e-money card issuers for losses incurred by their clients. Due to imprecise compensation procedures for the issuer, the issuer's legal responsibility is legally deficient, which frequently produces legal doubt for the protection of customers. It renders the e-money issuer legally immune from liability. In particular, this research attempts to create legal comparisons to demonstrate that the compensation and liability mechanism is not exhaustive, using UU No. 8, 1999 on Consumer Protection as an example. This research also discusses compensation for losses incurred by Bank Mandiri customers as a result of the incomplete compensation process outlined in Bank Indonesia Regulation Number 20/6 / PBI / 2018. This study is a legal normative study using a statutory approach (statute approach) and a case study approach (case approach). This research uses literary studies as its method of data collection. Through his or her review of the relevant literature, the researcher gathered and examined several documents using content analysis. The findings of this study demonstrate that the issuer of electronic money cannot be held liable for losses caused by client error. This compensation mechanism can only be used if the error was committed by the electronic money issuer and was determined to be incompatible with the Consumer Protection Law, which prioritizes consumer rights.